Strategi Pemerintah Desa dalam Mewujudkan Administrasi yang Transparan dan Akuntabel - Moh As’adi; Zaki Al Mubarok (Jurnal Manajemen dan Ilmu Administrasi, 2026)
Transparency and accountability are important principles in village governance that serve to realize good governance. This study aims to analyze the strategies employed by village governments in establishing transparent and accountable administration, as well as to examine various efforts undertaken to improve the quality of village governance. This research employed a qualitative approach using a case study design. Data were collected through interviews, observations, and documentation involving the village head, village officials, members of the Village Consultative Body (BPD), and community members as research informants. Data analysis was conducted using the model developed by Miles, Huberman, and Saldaña, which includes data collection, data condensation, data display, and conclusion drawing. The validity and credibility of the data were ensured through source triangulation and technique triangulation. The findings indicate that the village government's strategies for achieving administrative transparency include providing easily accessible public information, conducting village deliberation meetings, involving community members in decision-making processes, and utilizing information technology as a medium for information dissemination and administrative services. Meanwhile, the strategies for achieving administrative accountability include strengthening a well-organized and systematic administrative system, improving the competence of village officials, reinforcing supervisory mechanisms, and implementing information technology-based administrative systems. These strategies have proven effective in enhancing information openness, strengthening the accountability of village governments, increasing community participation, and building public trust in village governance. Therefore, administrative transparency and accountability are essential factors in creating a professional, effective, and community-oriented village government.